ANALISIS KOMPARATIF KECEPATAN PERPUTARAN UANG DI INDONESIA: SEBELUM DAN SESUDAH PANDEMI COVID-19 - Irdiansyah Irdiansyah (Prodi Pendidikan Ekonomi Universitas Mulawarman, 2025)
This study aims to comparatively analyze the velocity of money turnover in Indonesia before and after the COVID-19 pandemic. This research uses quantitative methods with a comparative descriptive analysis form, which compares the speed of money turnover in Indonesia in the period before and after the COVID-19 pandemic. The money velocity data used for the period before the pandemic is data from 2016-2019. Meanwhile, in the period after the pandemic the data used is data for 2020-2023. The normality test used is the Shapiro-Wilk test. This study uses the Wilcoxon Matched-Pairs signed-rank test, which is a non-parametric analysis hypothesis test. Based on the results of the study, there is no significant difference in the speed of money circulation in Indonesia before and after the COVID-19 pandemic. The significance value (sig.) of the comparison between the speed of money circulation before and after the announcement of the first confirmed case of COVID-19 in Indonesia is 0.0679, which is greater than 0.05.